Eutectic Nano/Microstructure: New Self‐Organization Route to Tunable Narrowband Optical Filters and Polarizers Demonstrated with ZnO–ZnWO4 Eutectic Composite (Advanced Optical Materials 7/2020). Issue 7 (6th April 2020) - Osewski, Paweł; Belardini, Alessandro; Centini, Marco; Valagiannopoulos, Constantinos; Leahu, Grigore; Li Voti, Roberto; Tomczyk, Monika; Alù, Andrea; Pawlak, Dorota A.; Sibilia, Concita
Abstract : A new ZnO–ZnWO4 eutectic composite manifests sharp and strongly polarization‐dependent transmission at ≈400 nm. Such a powerful effect is due to the formation of a fine self‐organized eutectic nano/microstructure that enables refractive index matching due to the proper orientation of the constituent phases. These functionalities are obtained by fabricating ZnO–ZnWO4 using a self‐organization low‐cost procedure, paving the way for large‐scale applications, such as tunable narrow‐band color filters. For further details see article number 1901617 by Dorota A. Pawlak and co‐workers.